PENGARUH GAYA KEPEMIMPINAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. ISS INDONESIA INDOSIAR - KOMPLEK JAKARTA BARAT - Hendri; Yan Kristian Halomoan (Journal of Research and Publication Innovation, 2024)
This study ains to determine the effect of leadership style and training on the performance of PT. ISS Indonesia west Jakarta, partially and simultaneously. The method used in this method is a quantitative approach,the population is 92  people by taking a saturated sample or the whole, with a sample of 92 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, detemnination analysis and hypotheisis testing. Based on the result of the analysis,obtained the value of F hitung > Ftabel (13.861> 3.10) this is also strengthened by a significance value of 0.000 < 0.05 so that it can be concluded that H03 is rejected and Ha3 is accepted. It can be concluded that leadership style (X1) and training (X2) simultaneosly affect employee performance (Y) .